Properties and Bifunctional Catalytic Activity of Niobium-Doped Silica-Titania: Effect of Phosphoric Acid Treatment - Siew Ling Lee; Jamilah Mohd Ekhsan; Chui Min Ling (Science and Technology Indonesia, 2022)
The effect of phosphoric acid treatment on the physical-chemical properties and catalytic activity of the niobium-doped silica-titania bifunctional catalyst was investigated. As part of the synthesis procedure to produce xPO4−/Nb/TiO2-SiO2, different concentrations of phosphoric acid (H3PO4) were used (x= 0, 0.05, 0.10, 0.15, 0.20, 0.25 M). As shown by XRD analysis, the samples synthesized using 0–0.20 M H3PO4 were in amorphous form, as featureless diffractograms were obtained, indicating the PO4− groups were dispersed homogeneously on the surface of Nb doped SiO2-TiO2. Due to the increased concentration of acid, other compounds were formed in the samples by reactions between PO4− and Nb and/or Ti. Additionally, UV-Vis DRS results indicated that the presence of the PO4− group accelerated the transformation of hydrated tetrahedral Ti species into isolated tetrahedral Ti species. An experimental investigation of the catalytic performance of the catalyst was conducted using 1,2-epoxyoctane as an oxidant for the epoxidation of 1-octene to 1,2-octanediol. It has been demonstrated that H3PO4 treatment was essential for oxidative and acidity active site formation. The current research findings strongly suggested that Nb-doped TiO2-SiO2 treated with 0.2 M H3PO4 was the most effective bifunctional catalyst in generating 1,2-octanediol.